EDUKASI PENTINGNYA MENABUNG USIA DINI BAGI SISWA SD NEGERI 1 RUMAHTIGA, AMBON - Huwae, Laury Marcia Chara; Anggrek, Sevennia; Avriyanti, Adivya; Tulalessy, Nielmark; Liklikwatil, Devita; Hartati, Dwi; Buton, Musrifa (Balobe: Jurnal Pengabdian Masyarakat, 2024)
Community Service is an obligation that must be fulfilled by university personnel, including lecturers and students. In Batch L KKN Period II for the 2023/2024 Academic Year, we carried out community service to students at SD Negeri 1 Rumahtiga - Ambon about the importance of saving at an early age. It is hoped that this education can motivate children to instill understanding and knowledge about the importance of saving at an early age to determine the future. Developing the habit of saving is a character that needs to be developed in early childhood. The concrete nature of child development is very effective in instilling a culture where saving determines the future. Students come to know and understand the benefits of saving for themselves. Apart from that, to develop and strengthen children's awareness of saving, parents need to be role models, and introduce the value of money, and how to set aside pocket money for savings.